(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
The article is devoted to the use of Internet resources in the modern practice of teaching Russian as a foreign language (hereinafter - RCT). Currently, a huge number of training resources on RCTs are being created and uploaded to the World Wide Web, but the format for their integration into the educational process has not yet been established. The relevance of this study is due to the need to determine the effectiveness of educational Internet resources.